Optimal energy rendering approach from lightning return stroke - Chowdhury, A.S.M. Mishkat Hussain; Hossen, MD. Sakib; Tabassum, Humaira (BRAC University, 2016)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2016.